2022
DOI: 10.3390/cancers14174333
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of PD-1/PD-L1 Inhibitors in Patients with Liver Metastasis of Non-Small Cell Lung Cancer: A Real-World Study

Abstract: Background: A controversy exists regarding the efficacy of programmed death-1 (PD-1)/ programmed death ligand-1 (PD-L1) inhibitors for patients with non-small cell lung cancer (NSCLC) and liver metastases. Our study retrospectively evaluated the efficacy of PD-1/PD-L1 inhibitors in NSCLC patients with liver metastases. Methods: This retrospective study included 1627 lung cancer patients who received immunotherapy. Among 648 patients who had advanced NSCLC and received PD-1/PD-L1 inhibitors, 61 had liver metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Another retrospective study suggested that ICIs combined with cytotoxic agents may be more effective than ICIs alone in NSCLC with liver metastasis [ 19 ]. Another Real-World Study came to a similar conclusion [ 20 ], among 648 patients with advanced NSCLC treated with ICIs, 61 of whom developed LMs. The results showed that patients with LMs receiving PD-1/PD-L1 inhibitors were effective (ORR: 29.5%, disease control rate: 72.1%, PFS: 6.4 months, OS: 15.2 months).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Another retrospective study suggested that ICIs combined with cytotoxic agents may be more effective than ICIs alone in NSCLC with liver metastasis [ 19 ]. Another Real-World Study came to a similar conclusion [ 20 ], among 648 patients with advanced NSCLC treated with ICIs, 61 of whom developed LMs. The results showed that patients with LMs receiving PD-1/PD-L1 inhibitors were effective (ORR: 29.5%, disease control rate: 72.1%, PFS: 6.4 months, OS: 15.2 months).…”
Section: Introductionmentioning
confidence: 64%
“…Another study also found phenotypic changes of CD8+ tumour-infiltrating lymphocytes (TILs) in distal biopsy site of patients with liver metastasis, supporting the possibility that invasion of cancer cells into the liver may trigger liver-specific tolerance mechanisms, thereby reducing the efficacy of systemic antitumor immunotherapy [ 38 ]. Other studies have found that CD8+ T cell infiltration in liver lesions is significantly less than in non-liver lesions, suggesting that liver metastasis is related to CD8+ T cells and may influence treatment outcomes through liver-induced peripheral tolerance [ 3 , 20 ].…”
Section: Tumour Microenvironment and Immunotherapy Mechanisms Of Icis...mentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor mutation burden and programmed death receptor ligand-1 and 1 (PD-L1 and PD-1, respectively), as well as the number and percentage of lymphocytes, are biomarkers for the occurrence of metastasis in NSCLC. PD-1 and PD-L1 inhibitors are most studied and applied currently, and have good therapeutic effects in patients with brain, [10][11][12] liver, 13,14 and bone metastases. 15 Primarily, ICIs assist immune cells in eliminating tumor cells by obstructing their ability to evade the immune system, which thus amplifies their antitumor impact.…”
Section: Introductionmentioning
confidence: 99%